2006
DOI: 10.1080/09709274.2006.11905853
|View full text |Cite
|
Sign up to set email alerts
|

Economics of Fish Demands in Lagos State, Nigeria

Abstract: This study analysed the economics of fish demands in Lagos State, Nigeria. Primary data were collected from a total of 110 fish consumers using multistage sampling procedure. Data were collected on household consumption activities for 2002 consumption period. The data were analysed using descriptive statistics and regression analysis. The results showed that the average sampled consumers are literate with mean household size of 5. It was evident from the study that, the higher the income level of the responden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 0 publications
3
25
0
Order By: Relevance
“…Also, 57.3% of the respondents are married with majority (68.54%) having household size of between 1 and 5. The dominant age range indicated a youthful age therefore the respondents tends to be well informed and provide genuine information, the occurrence of majority with tertiary education have good tendency of influencing their fish consumption and demand because consumers with a high level of education are more concerned about their health than those with a low level of education and this is in line with the findings of Amao et al (2006) and Dalhatu and Ala (2010). The marital status of the respondents with majority married may also have positive impact on frozen fish consumption though the relatively small size of households may be another limiting factor; also the higher percentage being civil servant implies a tendency for high income and consequently high demand for frozen fish (Onyeneke and Nwaiwu, 2012).…”
Section: Resultssupporting
confidence: 78%
See 1 more Smart Citation
“…Also, 57.3% of the respondents are married with majority (68.54%) having household size of between 1 and 5. The dominant age range indicated a youthful age therefore the respondents tends to be well informed and provide genuine information, the occurrence of majority with tertiary education have good tendency of influencing their fish consumption and demand because consumers with a high level of education are more concerned about their health than those with a low level of education and this is in line with the findings of Amao et al (2006) and Dalhatu and Ala (2010). The marital status of the respondents with majority married may also have positive impact on frozen fish consumption though the relatively small size of households may be another limiting factor; also the higher percentage being civil servant implies a tendency for high income and consequently high demand for frozen fish (Onyeneke and Nwaiwu, 2012).…”
Section: Resultssupporting
confidence: 78%
“…The level of education of the frozen fish consumer has a positive coefficient with fish demand, implying that an increase in the level of education of a consumer leads to an increase in quantity of fish demanded. This could be attributed to the fact that educated people are more aware of the nutritive value of fish as a good protein source (Amao et al, 2006). The type of frozen fish (Mackerel, Horse mackerel and Sardinella) available also determines the quantity of frozen fish consumed by the respondents.…”
Section: Resultsmentioning
confidence: 99%
“…This positive sign is consistent with the apriori expectation which implies that prices of substitutes were directly related to fish demand expenditure. In the study of economics of fish demand in Lagos State, Amao et al (2006) found that the fish consumers with income less than N10,000 and income between N10,000 to N20,000 spent more on substitutes than fish. The authors further pointed out that this might be due to the relative cheapness of the substitutes in the study area.…”
Section: Methodsmentioning
confidence: 99%
“…According to Alexandratos (2000), the ever increasing share of fish in animal protein intake and total protein supply implies that fish has become more and more important in people's diet. Over the past 15 years, fish has enjoyed an explosive increase in demand around the world; a demand that has also boosted its price (Amao et al, 2006). The authors indicated that there is heightened awareness in the developed world of the nutritional and health benefits of fish products which are low in fat and calories and high in protein, vitamins, minerals and polyunsaturated fatty acids.…”
Section: Introductionmentioning
confidence: 99%
“…In Nigeria today and Bayelsa state in particular, there is need to increase fish production because fish products are relatively cheaper compared to beef, pork and other animal protein sources [1]. Fish production in Nigeria is from artisanal fisheries, industrial or commercial trawlers and fish farming in ponds.…”
Section: Introductionmentioning
confidence: 99%